Caffeine and carbohydrate supplementation during exercise when in negative energy balance: effects on performance, metabolism, and salivary cortisol - Slivka, D.; Hailes, W.; Cuddy, J.; Ruby, B. (Applied Physiology, Nutrition, and Metabolism, 2008)
The ingestion of carbohydrate (+CHO) and caffeine (+CAF) during exercise is a commonly used ergogenic practice. Investigations are typically conducted with subjects who are in a rested state after an overnight fast. However, this state of positive energy balance is not achieved during many work and exercise circumstances. The aim of this study was to evaluate the substrate use and performance effects of caffeine and carbohydrate consumed alone and in combination while participants were in negative energy balance. Male participants (n = 9; 23 ± 3 years; 74.1 ± 10.6 kg) completed 4 trials in random order: -CAF/-CHO, -CAF/+CHO, +CAF/-CHO, and +CAF/+CHO. Diet and exercise were prescribed for 2 days before each trial to ensure negative energy balance. For each trial, before and after 2 h of cycling at 50% of maximal watts, a saliva sample and a muscle biopsy (vastus lateralis) were obtained. A simulated 20 km time trial was then performed. The respiratory exchange ratio was higher (p < 0.05) in +CHO trials and lower (p < 0.05) in the +CAF/+CHO trial than in the -CAF/+CHO trial. Salivary cortisol response was higher (p < 0.05) in the +CAF/-CHO trial than in any of the other trials. Muscle glycogen and heart rates were similar in all trials. Performance in the 20 km time trial was better in the -CAF/+CHO trial than in the -CAF/-CHO trial (p < 0.05), but the +CAF/+CHO trial was no better than the +CAF/-CHO trial (p > 0.05), or any of the other trials. When co-ingested with carbohydrate, caffeine increased fat use and decreased nonmuscle glycogen carbohydrate use over carbohydrate alone when participants are in negative energy balance; however, caffeine had no effect on the 20 km cycling time trial performance.